Hybrid Natural-Synthetic Fiber Composites for Noise and Vibration Control: Linking Acoustic Performance to Environmental Sustainability Metrics - Fauzi Ibrahim; Rani Ismiarti Ergantara; Ambar Pambudi (Journal of Fibers and Polymer Composites, 2026)
Hybrid natural-synthetic fiber composites are attractive for automotive acoustic trim only when composition effects are separated from geometric effects and the computational assumptions are fully reproducible. This study presents a transparent screening framework linking normal-incidence acoustic absorption, a literature-informed vibration-damping proxy, specific stiffness, mass and constituent-production environmental metrics. Twelve polypropylene-based formulations were compared at a common thickness of 20 mm; 16, 20 and 24 mm were then evaluated separately in the thickness-sensitivity analysis. Open porosity and flow resistivity were generated by explicit bounded composition-to-property rules and used in the Miki equivalent-fluid model. Environmental inputs were evaluated with 20,000-trial triangular uncertainty propagation, while the multi-criteria ranking used winsorized normalization and 10,000 weight-perturbation scenarios of +/-15%. At 20 mm, broadband absorption averages (500-4000 Hz) occupied a narrow range of 0.612-0.636, demonstrating that acoustic comparisons are sensitive to geometry and that thickness must be controlled when isolating composition effects. Increasing thickness from 16 to 24 mm raised the modeled broadband absorption of representative natural-fiber-rich panels from about 0.55 to 0.69. C25-G10-R5 ranked first under the baseline weights and in 100% of weight-perturbation scenarios; JC30-G10 remained in the top three in 100% of scenarios and C35-rP5 in 79.1%. Median constituent-production greenhouse-gas reductions relative to GF40-PP ranged from approximately 26% to 56% for the non-aramid hybrid candidates, whereas the aramid-containing design was environmentally unfavorable. The reported damping values are screening proxies, not measured loss factors, and the environmental calculation is not a full ISO-compliant comparative LCA. The framework is therefore intended for hypothesis generation and experimental down-selection rather than direct certification of material performance.